Genomic Instability of Mutation-Derived Gene Prognostic Signatures for Hepatocellular Carcinoma - Song, Ze-Bing; Yu, Yang; Zhang, Guo-Pei; Li, Shao-Qiang (Frontiers in Cell and Developmental Biology, 2021)
Hepatocellular carcinoma (HCC) is one of the major cancer-related death worldwide. Genomic instability is correlated with the prognosis of cancers. A biomarker associated with genomic instability might be effective to predict the prognosis of HCC. In the present study, data of HCC patients from The Cancer Genome Atlas (TCGA) and International Cancer Genome Consortium (ICGC) databases were used. A total of 370 HCC patients from the TCGA database were randomly classified into a training and a test set. A prognostic signature of the training set based on nine overall survival (OS)-related genomic instability-derived genes (SLCO2A1, RPS6KA2, EPHB6, SLC2A5, PDZD4, CST2, MARVELD1, MAGEA6, and SEMA6A) was constructed, which was validated in the test, TCGA and ICGC sets. This prognostic signature showed more accurate prediction for prognosis of HCC compared with tumor grade, pathological stage and four published signatures. Cox multivariate analysis revealed that the risk-score could be an independent prognostic factor of HCC. A nomogram that combines pathological stage and risk-score performed well compared with an ideal model. Ultimately, paired differential expression profiles of genes in the prognostic signature were validated at mRNA and protein level using HCC and para-tumor tissues obtained from our institute. Taken together, we constructed and validated a genomic instability derived genes prognostic signature which can help to predict the OS of HCC and help us to explore the potential therapeutic targets of HCC.